Awareness about Face Bow and its Types among Dental Professionals- A Questionnaire Based Survey - Venkatesh Kommi1 , Reethega L2 , Keerthi Sasanka.L3 , Venkatesh Kommi4 , Geetha.R.V5 , Dhanraj Ganap (Institute of Medico-legal Publications Pvt Ltd, 2020)
A face bow is a caliper like instrument used to record spatial relation from maxillary arch to the anatomicalpoints and transfer the jaw relation to an articulator. It orients the dental cast in the same relationship tothe opening axis of the articulator. There are mainly two types of face bows - Kinematic and Arbitraryface bows. Arbitrary face bows inturn have many subtypes based on anterior and posterior reference pointindicators and the mechanism of inter condylar distance equilibrium.The questionnaire containing questionsabout face bows and its types was circulated to about 100 participants through google docs - online survey.The study was approved ethically by IERB.The responses generated from the survey were converted intopie charts and recorded. The answers obtained are discussed by comparing with the previous articles.Thesurvey study shows how much Dental professionals know about face bows and its types and implementingthem in their practice.